Cochlear Synaptopathy Changes Sound-Evoked Activity Without Changing Spontaneous Discharge in the Mouse Inferior Colliculus - Shaheen, Luke A.; Liberman, M. Charles (Frontiers in Systems Neuroscience, 2018)
Tinnitus and hyperacusis are life-disrupting perceptual abnormalities that are often preceded by acoustic overexposure. Animal models of overexposure have suggested a link between these phenomena and neural hyperactivity, i.e. elevated spontaneous rates (SRs) and sound-evoked responses. Prior work has focused on changes in central auditory responses, with less attention paid to the exact nature of the associated cochlear damage. The demonstration that acoustic overexposure can cause cochlear neuropathy without permanent threshold elevation suggests cochlear neuropathy per se may be a key elicitor of neural hyperactivity. We addressed this hypothesis by recording responses in the mouse inferior colliculus (IC) following a bilateral, neuropathic noise exposure. One to three wks post-exposure, mean SRs were unchanged in mice recorded while awake, or under anesthesia. SRs were also unaffected by more intense, or unilateral exposures. These results suggest that neither neuropathy nor hair cell loss are sufficient to raise SRs in the IC, at least in 7-wk-old mice, one to three wks post exposure. However, it’s not clear whether our mice had tinnitus. Tone-evoked rate-level functions at the CF were steeper following exposure, specifically in the region of maximal neuropathy. Furthermore, suppression driven by off-CF tones and by ipsilateral noise were also reduced. Both changes were especially pronounced in neurons of awake mice. This neural hypersensitivity may manifest as behavioral hypersensitivity to sound - prior work reports that this same exposure causes elevated acoustic startle. Together, these results indicate that neuropathy may initiate a compensatory response in the central auditory system leading to the genesis of hyperacusis.